Comparing the effects of self-selected music versus predetermined music on patient anxiety prior to gynaecological surgery: a study protocol for a randomised controlled trial - Tiphaine Petot; Nicolas Bouscaren; Olivier Maillard; Laetitia Huiart; Malik Boukerrou; Danielle Reynaud (Trials, 2019)
Abstract Background Patients undergoing gynaecological surgery are known to experience anxiety. While the use of music selected by patients based on their personal taste has hardly been evaluated, a recent study suggests that musical preferences significantly alter the anxiolytic and relaxing effects of music. Our study aims to determine whether self-selected music decreases patient anxiety prior to gynaecological surgery, as compared with predetermined music from a software programme such as MUSIC CARE®. Methods The study will consist of a clinical trial comparing the effects of self-selected music versus predetermined music on patient anxiety prior to gynaecological surgery. A minimum of 170 patients will be randomised in a 1:1 ratio. Inclusion criteria will be: women aged 18–55 years, awaiting scheduled gynaecological surgery under general/local anaesthesia or under sedation; having created a personal 20-min playlist; and not having received anxiolytic drugs prior to surgery. The primary outcome will be the difference between the preoperative anxiety score taken 15 to 20 min before the music-listening session and the preoperative anxiety score taken shortly after the session, as measured with the STAI for state anxiety. Discussion This study should help to identify more effective non-medical treatments for preoperative anxiety, as well as to adapt music therapy to the cultural context of patients. Trial registration ClinicalTrials.gov, ID: NCT03226834. Registered on 24 July 2017.